Continuous flow synthesis of a carbon-based molecular cage macrocycle via a three-fold homocoupling reaction1. Issue 75 (28th September 2015) - Kitchin, Melanie; Konstas, Kristina; Sumby, Christopher J.; Czyz, Milena L.; Valente, Peter; Hill, Matthew R.; Polyzos, Anastasios; Doonan, Christian J.
<x xml:space="preserve">Abstract</x> The facile synthesis of the cage molecule (C110H56Br2) via a remarkable three-fold homo-coupling macrocyclization reaction using continuous flow methodology is reported.